Are cash flows relevant for stock pricing in Bursa Malaysia? - Cheng, Fan Fah; Ramadilli Mohd, Shamsher Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The research on whether information on cash flows have any impact beyond earnings disclosures has inconclusive results. Changes in cash flows are found to have significant impact beyond that of earnings only if share price changes are measured over a short window of about 3 days and not over a long window of say annual or 51 days windows. The results show that cash flow changes measured over one-year intervals did not affect share prices. This is also reconfirmed using the portfolio approach. To recapitulate, though cash flows appear to have no information content on share prices in the annual and medium windows tests, it does have information content in the short window tests with incremental information content beyond earnings, implying it has relevant value information though investors are more comfortable with earnings announcements for share price valuation. This finding reported from an emerging economy is consistent with evidence from developed markets.